Contribution of Arm Muscle Strength to Service Ability in Youth Football Games in Benteng Village, Sungai Batang District - Saifullah, Saifullah; Apriani , Leni (Universitas Majalengka, 2024)
This study aims to determine the contribution of arm muscle strength to serving ability in youth volleyball games in Beneteng sub-district, Sungai Batang sub-district. The method used is the correlation method, namely the correlation analysis technique with product moment statistics. This research used a sample of 15 athletes taken using a sampling technique. The research population was teenagers from Bententeng sub-district, Sungai Batang sub-district. The research sample was 15 people taken with an age limit of 15 years. Data collected in this study used instruments (1) arm muscle strength test, (2) Volleyball Upper Serve Skills test. . Based on the r table obtained for sample 15, the r table is obtained at 0.65. So hypothesis testing can be carried out, namely if the calculated r is greater than the r table then the alternative hypothesis is accepted. Based on the results obtained, it can be seen that the calculated r (0.409) is smaller than the table r (0.412), therefore it can be concluded that there is no relationship between arm muscle strength and upper serve results in male youth volleyball athletes in Benteng Village, Sungai Batang District. While the contribution is 16.72%,